2021
DOI: 10.3390/jcm10214904
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Gestational Diabetes Diagnostic Criteria during the Pandemic: An Observational Study

Abstract: Objective: To analyze the effect of applying alternative diagnostic criteria for gestational diabetes mellitus (GDM) during the COVID-19 pandemic on GDM prevalence and obstetrical and perinatal outcomes, in comparison to usual diagnostic approaches. Methods: Data from women referred to GDM diagnosis from 1 September to 30 November 2019 were retrospectively collected (2019-group). The same data from the same period in 2020 were prospectively collected (2020-group). In both cases, a two-step diagnostic approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
8
2
Order By: Relevance
“…Our findings do not support retrospective studies that modelled pregnancy outcomes associated with the emergency GDM care pathways, and suggested that adverse outcomes may be increased because women who would have normally been diagnosed with GDM may be ‘missed’ 16 . Consistent with our findings is a prospective study in Spain that found that the rate of missed diagnoses of GDM did not substantially change when comparing conventional criteria used before the pandemic with alternative diagnostic criteria used during the pandemic 38 . A nationwide cohort study of 948 020 singleton births in England, comparing maternal and neonatal outcomes for the general maternity population during COVID‐19 and in the year prior, found an increase in obstetric intervention 39 .…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Our findings do not support retrospective studies that modelled pregnancy outcomes associated with the emergency GDM care pathways, and suggested that adverse outcomes may be increased because women who would have normally been diagnosed with GDM may be ‘missed’ 16 . Consistent with our findings is a prospective study in Spain that found that the rate of missed diagnoses of GDM did not substantially change when comparing conventional criteria used before the pandemic with alternative diagnostic criteria used during the pandemic 38 . A nationwide cohort study of 948 020 singleton births in England, comparing maternal and neonatal outcomes for the general maternity population during COVID‐19 and in the year prior, found an increase in obstetric intervention 39 .…”
Section: Discussioncontrasting
confidence: 75%
“…16 Consistent with our findings is a prospective study in Spain that found that the rate of missed diagnoses of GDM did not substantially change when comparing conventional criteria used before the pandemic with alternative diagnostic criteria used during the pandemic. 38 A nationwide cohort study of 948 020 singleton births in England, comparing maternal and neonatal outcomes for the general maternity population during COVID-19 and in the year prior, found an increase in obstetric intervention. 39 We had no information about whether women were included in both Pre-and COVID populations and so were not able to adjust for this in our analyses.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Meanwhile, a prospective study by Molina-Vega et al. found that the rate of missed diagnosis of GDM did not substantially change when comparing conventional criteria used before the pandemic with alternative diagnostic criteria used during the COVID-19 pandemic ( 42 ). Therefore, more studies are needed to examine the effects of diagnosis criteria on the association between COVID-19 lockdown and GDM.…”
Section: Discussionmentioning
confidence: 99%
“…17 Most of the studies examining the impact of modified screening protocols are based on either cohorts of women prior to the pandemic or single-centre experiences. 6,10,[17][18][19][20][21][22][23] There are currently limited real-world data on the uptake of the modified screening guidelines, their impact on the rates of GDM diagnosis and associated outcomes at the population level.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that women who had a missed GDM diagnosis had worse pregnancy and neonatal outcomes than women with no GDM for both the modified UK and Canadian guidelines, but not the modified Australian criteria 17 . Most of the studies examining the impact of modified screening protocols are based on either cohorts of women prior to the pandemic or single‐centre experiences 6,10,17‐23 . There are currently limited real‐world data on the uptake of the modified screening guidelines, their impact on the rates of GDM diagnosis and associated outcomes at the population level.…”
Section: Introductionmentioning
confidence: 99%